Considerations for Pooled Testing of Employees for SARS-CoV-2 - Schulte, Paul A. (J Occup Environ Med, 2021)
To identify important background information on pooled tested of employees that employers workers, and health authorities should consider. METHODS: This paper is a commentary based on the review by the authors of pertinent literature generally from preprints in medrixiv.org prior to August 2020. RESULTS/CONCLUSIONS: Pooled testing may be particularly useful to employers in communities with low prevalence of COVID-19. It can be used to reduce the number of tests and associated financial costs. For effective and efficient pooled testing employers should consider it as part of a broader, more comprehensive workplace COVID-19 prevention and control program. Pooled testing of asymptomatic employees can prevent transmission of SARS-CoV-2 and help assure employers and customers that employees are not infectious.